Measurement investigation of tap and cluster angular spreads at 5.2 GHz - Kai Yu; Qinghua Li; Ho, M. (IEEE transactions on antennas and propagation, 2005)
In this paper, we present indoor measurement results on the cluster angular spread (AS), the tap AS and its variation with different channel bandwidths. A frequency domain space alternating generalized expectation maximization (FD-SAGE) algorithm is employed to estimate the multipath components from the measured data. We then manually identify the clusters of the multipaths and calculate the tap and cluster ASs for each identified cluster. It is found that for the 100 MHz channels, the average tap AS is just few degrees less than the cluster AS and the difference diminishes for less channel bandwidth.